The use of artificial intelligence for delivery of essential health services across WHO regions: a scoping review - Okeibunor, Joseph Chukwudi; Jaca, Anelisa; Iwu-Jaja, Chinwe Juliana; Idemili-Aronu, Ngozi; Ba, Housseynou; Zantsi, Zukiswa Pamela; Ndlambe, Asiphe Mavis; Mavundza, Edison; Muneene, Derrick; Wiysonge, Charles Shey; Makubalo, Lindiwe (Frontiers in Public Health, 2023)
Background: Artificial intelligence (AI) is a broad outlet of computer science aimed at constructing machines capable of simulating and performing tasks usually done by human beings. The aim of this scoping review is to map existing evidence on the use of AI in the delivery of medical care. Methods: We searched PubMed and Scopus in March 2022, screened identified records for eligibility, assessed full texts of potentially eligible publications, and extracted data from included studies in duplicate, resolving differences through discussion, arbitration, and consensus. We then conducted a narrative synthesis of extracted data. Results: Several AI methods have been used to detect, diagnose, classify, manage, treat, and monitor the prognosis of various health issues. These AI models have been used in various health conditions, including communicable diseases, non-communicable diseases, and mental health. Conclusions: Presently available evidence shows that AI models, predominantly deep learning, and machine learning, can significantly advance medical care delivery regarding the detection, diagnosis, management, and monitoring the prognosis of different illnesses.